Intercept-Resend Attack on SARG04 Protocol: An Extended Work - Ali H. Yousif; Omar S. Mustafa; Dana F. Abdulqadir; Farah S. Khoshaba (Polytechnic Journal)
In this paper, intercept/resend eavesdropper attack over SARG04 quantum key distribution protocol is investigated by bounding the information of an eavesdropper; then, the attack has been analyzed. In 2019, simulation and enhancement of the performance of SARG04 protocol have been done by the same research group in terms of error correction stage using multiparity rather than single parity (Omar, 2019). The probability of detecting the case in the random secret key by eavesdropper is estimated. The results of intercept/resend eavesdropper attack proved that the attack has a significant impact on the operation of the SARG04 protocol in terms of the final key length.